The Influence of Kentucky Fried Chicken’s Logistic Service Quality Towards Customer Satisfaction and Customer Loyalty in Surabaya - Yohji Ericko; Raymond Hendry; Dr. Michael Adiwijaya (Jurnal Hospitality dan Manajemen Jasa, 2015)
Kentucky Fried Chicken is fast food restaurant  that serves chicken products and other products related to chicken. The number of fast food restaurants growth in Indonesia leads to competition between fast food restaurant in presenting a good product and service quality for customer. Kentucky Fried Chicken should maintain the quality of their products and services if Kentucky Fried Chicken do not want their customers move to another restaurant. To improve the quality of service Kentucky Fried Chicken provide delivery service to provide a convenience way for customers who are reluctant to queue up at the location. The analysis technique used in this research is quantitative using Structural Equation Modeling ( SEM ) method with Smart PLS ( Partial Least Square ) software.